Malaria outbreak response in urban Santo Domingo, Dominican Republic: lessons learned for community engagement - Dianelba Valdez; Hunter Keys; Keyla Ureña; Domingo Cabral; Francisco Camilo; Eulalia C. Ogando; Luz Mercedes; Gregory S. Noland; Stephen B. Blount; James V. Lavery; Luccene Desir; Jose Puello (Pan American Health Organization, 2020)
Community engagement is crucial for public health initiatives, yet it remains an under-studied process within national disease elimination programs. This report shares key lessons learned for community engagement practices during a malaria outbreak response in the Los Tres Brazos neighborhood of urban Santo Domingo, Dominican Republic from 2015-2016. In this two-year period, 233 cases of malaria were reported-more than seven times the number of cases (31) reported in the previous two years. The initial outbreak response by the national malaria program emphasized "top-down" interventions such as active surveillance, vector control, and educative talks within the community. Despite a transient reduction in reported cases in mid-2015, transmission resurged at the end of 2015. The program responded by introducing active roles for trained community members that included door-to-door fever screening, testing with rapid diagnostic tests and treatment. Malaria cases declined significantly throughout 2016 and community-based active surveillance infrastructure helped to detect and limit a small episode of transmission in 2017. Results from qualitative research among community members revealed two key factors that facilitated their cooperation with community-based surveillance activities: motivation to help one's community; and trust among stakeholders (community health workers, their neighbors and other key figures in the community, and malaria program staff and leadership). This experience suggests that community-led interventions and the program's willingness to learn and adapt under changing circumstances can help control malaria transmission and pave the way for elimination.